Settlement Process and Belief Characteristics of the Chinese People in the Southern Vietnam in the XVII-XIX Centuries - Van, Bui Thi Anh; Co, Nguyen Dinh; Nguyen, Tran Cao; Chi, Nguyen Tung Thao; Hiep , Tran Xuan (Journal of Ecohumanism, 2024)
The article clarifies the process of Chinese people coming to the Southern region and gradually shaping the cultural and religious characteristics in the area with the largest concentration of Chinese people in Vietnam. In the context of great upheavals in China at the end of the 17th century, a large number of Chinese people boarded boats to leave their homeland and go south to find the promised land. When the Chinese came to Vietnam, they brought traditional beliefs from their homeland to the new land as a way to support their lives in the new land, and at the same time they also integrated and continued to live. absorbing and adapting the beliefs of the communities that had previously settled here (especially the Vietnamese community) to create unique characteristics in the religious activities of the Chinese people in the Southern region. In addition, we will analyze and compare the beliefs of the Chinese people in the South with the beliefs originating from China to see the change and mixture between Chinese culture and the culture of other communities. Indigenous residents during the community settlement process..